2020
DOI: 10.3390/cells9051158
|View full text |Cite
|
Sign up to set email alerts
|

BHRF1 Enhances EBV Mediated Nasopharyngeal Carcinoma Tumorigenesis through Modulating Mitophagy Associated with Mitochondrial Membrane Permeabilization Transition

Abstract: Epstein–Barr virus (EBV) is a major contributor to nasopharyngeal carcinoma (NPC) tumorigenesis. Mitochondria have been shown to be a target for tumor viral invasion, and to mediate viral tumorigenesis. In this study, we detected that mitochondrial morphological changes in tumor tissues of NPC patients infected with EBV were accompanied by an elevated expression of BHRF1, an EBV encoded protein homologue to Bcl-2. High expression of BHRF1 in human NPC cell lines enhanced tumorigenesis and metastasis features. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Infection with Epstein-Barr virus (EBV), an oncovirus associated with Burkitt lymphoma, reduces mitochondria content in differentiating monocytes [ 109 ], remodels B cell mitochondria by targeting the mitochondrial 1-Carbon pathway involved in the synthesis of purine, thymidylate and glutathione [ 110 ] and also induces mitochondria swelling, cyclophilin D dependent mitochondrial membrane permeabilization transition (MMPT), decreased mitochondrial membrane potential (Δψm) and ATP, increased ROS production and mitophagy and reduced apoptosis [ 111 ]. Additionally, proteins of human papillomavirus (HPV) interact with mitochondria, promoting detachment of mitochondria from microtubules, reducing or eliminating cristae compartment, resulting in decreased Δψm, increased production of mtROS, oxidative stress and DNA damage [ 126 , 127 , 128 , 165 ].…”
Section: Mitochondrial Bioenergetics and Dynamics In Infectious Diseasesmentioning
confidence: 99%
“…Infection with Epstein-Barr virus (EBV), an oncovirus associated with Burkitt lymphoma, reduces mitochondria content in differentiating monocytes [ 109 ], remodels B cell mitochondria by targeting the mitochondrial 1-Carbon pathway involved in the synthesis of purine, thymidylate and glutathione [ 110 ] and also induces mitochondria swelling, cyclophilin D dependent mitochondrial membrane permeabilization transition (MMPT), decreased mitochondrial membrane potential (Δψm) and ATP, increased ROS production and mitophagy and reduced apoptosis [ 111 ]. Additionally, proteins of human papillomavirus (HPV) interact with mitochondria, promoting detachment of mitochondria from microtubules, reducing or eliminating cristae compartment, resulting in decreased Δψm, increased production of mtROS, oxidative stress and DNA damage [ 126 , 127 , 128 , 165 ].…”
Section: Mitochondrial Bioenergetics and Dynamics In Infectious Diseasesmentioning
confidence: 99%
“…The impact of BHRF1 protein on cell vitality was confirmed by several early and recent studies. Research showed that BHRF1 is able to protect the cell by conferring resistance to various apoptotic stimuli including γ-radiation and chemical compounds such as staurosporine, ionomycin, etoposide, roscovitine, methotrexate, and anti-IgM Fab2 antibody fragments [13,[84][85][86][87][88].…”
Section: Bhrf1mentioning
confidence: 99%
“…Infection by EBV, also known as HHV-4, causes various human malignancies, including posttransplant lymphoproliferative diseases, nasopharyngeal carcinoma, Hodgkin’s lymphoma, Burkitt lymphoma, and gastric carcinoma [ 54 ]. The EBV-encoded product BHRF1, a BCL2 homolog, is known to activate mitophagy via modulating mitochondrial dynamics or mitochondrial membrane permeabilization transition (MMPT) in BHRF1-transfected cervical (HeLa) or nasopharyngeal (CNE1 and 5-8F) cancer cell lines and EBV-reactivated AKATA cells [ 55 , 56 ]. BHRF1 expression stimulates DRP1-mediated mitochondrial fission and, concomitantly, autophagic flux by interacting with Beclin 1, thereby attenuating type-I IFN induction [ 55 ].…”
Section: Mitophagymentioning
confidence: 99%
“…The BHRF1-induced mitochondrial fission and autophagy stimulation lead to mitochondrial network reorganization to form juxtanuclear mitochondrial aggregates, which then cause the induction of mitophagy and the accumulation of PINK1 at the mitochondria. In addition, BHRF1 expression is known to induce cyclophilin D-dependent MMPT, which in turn increases ROS production and activates mitophagy in nasopharyngeal carcinoma cell lines [ 56 ]. In addition, the viral latent membrane protein 2A (LMP2A) has been shown to promote DRP1-mediated mitochondrial fission in stably transfected gastric and breast cancer cell lines, AGS and MCF7 respectively, suggesting that LMP2A-induced mitochondrial fission may contribute to tumorigenesis of EBV-associated epithelial cancers [ 57 ].…”
Section: Mitophagymentioning
confidence: 99%
See 1 more Smart Citation